2022
DOI: 10.1038/s41467-022-28205-y
|View full text |Cite|
|
Sign up to set email alerts
|

Sonogenetic control of mammalian cells using exogenous Transient Receptor Potential A1 channels

Abstract: Ultrasound has been used to non-invasively manipulate neuronal functions in humans and other animals. However, this approach is limited as it has been challenging to target specific cells within the brain or body. Here, we identify human Transient Receptor Potential A1 (hsTRPA1) as a candidate that confers ultrasound sensitivity to mammalian cells. Ultrasound-evoked gating of hsTRPA1 specifically requires its N-terminal tip region and cholesterol interactions; and target cells with an intact actin cytoskeleton… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 85 publications
1
44
0
Order By: Relevance
“…Mechanosensitive ion channels allow for the direct transduction of mechanical energy (e.g., US acoustic wave) into neural signals. These neural signals could also emanate from calcium influx in hs TRPA1-expressing mammalian human embryonic kidney-293T cells, which interact with the actin cytoskeleton inducing the calcium influx (Duque et al, 2022 ). The membrane conformational states have three general frameworks of voltage-induced changes: (1) membrane tension ( Figure 2 , (2) direct flexoelectricity ( Figure 2C ), and (3) thermodynamic waves ( Figure 2B ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanosensitive ion channels allow for the direct transduction of mechanical energy (e.g., US acoustic wave) into neural signals. These neural signals could also emanate from calcium influx in hs TRPA1-expressing mammalian human embryonic kidney-293T cells, which interact with the actin cytoskeleton inducing the calcium influx (Duque et al, 2022 ). The membrane conformational states have three general frameworks of voltage-induced changes: (1) membrane tension ( Figure 2 , (2) direct flexoelectricity ( Figure 2C ), and (3) thermodynamic waves ( Figure 2B ).…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, there are a family of proteins in ion channel the Homo sapiens transient receptor potential A1 ( hs TRPA1), which recently are found to have mechanosensitive properties (Duque et al, 2022 ). Duque and colleagues demonstrated that in vitro and in vivo sonication in rats and mice produced calcium influx and membrane currents in hs TRPA1-expressing mammalian human embryonic kidney-293T cells.…”
Section: Mechanisms For Neuromodulation Via Usmentioning
confidence: 99%
“…However, the findings of Yoo et al (2022) provide only a mechanistic explanation that ultrasound activates neurons by mechanosensitive calcium accumulation; they do not indicate the specific MS ion channels that are directly gated by ultrasound force. In contrast, Duque et al (2022) revealed that ultrasound evoking gating of hsTRPA1 specifically requires its N-terminal tip region and cholesterol interactions. The cytoskeletal elements are involved in the ultrasound sensitivity of hsTRPA1.…”
Section: Ultrasound For the Exploration Of Mechanosensitive Ion Channelsmentioning
confidence: 88%
“…The pore-forming subunits MEC-4 and MEC-10 may interact with the ECM proteins MEC-1, MEC-5, and MEC-9 and the tubulins MEC-7 and MEC-12 ( Chalfie, 2009 ). Two recently sonogenetic studies showed that ultrasonic neuromodulation is mediated by mechanical stress on the plasma membrane and relies on the intact organization of actin filaments ( Duque et al, 2022 ; Yoo et al, 2022 ). Yoo et al (2022) demonstrated ultrasound stimulation activating specific MS ion channels including TRPP1/2, TRPC1, and PIEZO1.…”
Section: Ultrasound For the Exploration Of Mechanosensitive Ion Channelsmentioning
confidence: 99%
“…Ultrasound has recently been used to trigger mechanosensitive K + , Ca 2+ , and Na + channels that are found in the retina and brain ( Maingret et al, 1999 ; Kubanek et al, 2016 ; Sorum et al, 2021 ). Those mechanosensitive proteins include MEC-4 ( Kubanek et al, 2018 ), TRPP1/2 ( Duque et al, 2022 ), TRPV1 ( Yang et al, 2020 ), Piezo 1 ( Qiu et al, 2019a ), MscL ( Ye et al, 2018 ), TRAAK ( Sorum et al, 2021 ), and the K2p family ( Zhao et al, 2017 ). Although it has not been fully understood, those mechanosensitive components are believed to play a critical role in neuromodulation using UST ( Ye et al, 2018 ).…”
Section: Working Principle Of Ultrasound Stimulationmentioning
confidence: 99%